Pola Spasial Permukiman Tradisional Bali Aga di Desa Sekardadi, Kintamani - Ni Ketut Agusintadewi (RUAS (Review of Urbanism and Architectural Studies), 2016)
The Bayung Gede village has derived smaller traditional settlements around Kintamani. Sekardadi is one of these settlements that has an inherent consociates with the village of origin, or the Bayung Gede. Despite the fact that the Sekardadi has a uniqueness on spatial pattern and house lay out, this village has not been welldocumented as an old village in Bali. These uniqueness are interesting to be indepth explored. It is not only on the basic philosophy of the house pattern, but also how this pattern to be physical implemented. This study aims to describe some characteristics of the village, both physical and nonphysical aspects, through the way of descriptive exploratory qualitative approach. According to the theory housing pattern of Habraken (1978) and Turgut (2001), research variables are determined into three variables: 1) Cultural setting; 2) Behavioural setting; and 3) Spatial setting. The result shows that macro spatial pattern of the Sekardadi village is divided into three zones: 1) Utama Mandala locates in the north of the village; 2) Madya Mandala is in the middle of the village, and 3) Nista Mandala in the south. Spatial pattern follows the hulu-teben conception or linear pattern with the main road as a cardinal orientation. Higher land means a sacred area (parahyangan) that is characterized by the existence of Pura Puseh. Meanwhile, the opposite is defined as a profane area (palemahan) with the presence of graves; and in the middle is the settlement (pawongan).Keywords: spatial pattern; traditional settlement; Sekardadi village